Adaptive Processing of Range Scanned Head: Synthesis of Personalized Animated Human Face Representation with Multiple-Level Radial Basis Function. (3rd December 2006) - Chen Chen, C. C.; Prakash Prakash, Edmond C. Edmond C.
Abstract : We propose an animation system for personalized human head. Landmarks compliant to MPEG-4 facial definition parameters (FDP) are initially labeled on both template model and any target human head model as priori knowledge. The deformation from the template model to the target head is through a multilevel training process. Both general radial basis function (RBF) and compactly supported radial basis function (CSRBF) are applied to ensure the fidelity of the global shape and face features. Animation factor is also adapted so that the deformed model still can be considered as an animated head. Situations with defective scanned data are also discussed in this paper.